1978
DOI: 10.1029/gl005i004p00317
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric ozone measurement with an infrared Heterodyne spectrometer

Abstract: A stratospheric ozone absorption line in the 10 µm band has been measured and resolved completely, using an infrared heterodyne spectrometer with a spectral resolution of 5 MHz (0.000167 cm−1). The vertical concentration profile of stratospheric ozone is obtained through an analytical inversion of the measured spectral line profile. The absolute total column density was 0.32 ± 0.02 cm‐atm with a peak mixing ratio occurring at ∼ 24 km. The (7,1,6) ‐ (7,1,7) O3 line center frequency was found to be 1043.1772 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Early LHRs used carbon dioxide gas lasers or lead salt lasers as the mid-infrared (mid-IR) local oscillators (LOs) and successfully targeted atmospheric ozone (O 3 ), nitrous oxide (N 2 O), and methane (CH 4 ) [4][5][6][7][8][9]. However, carbon dioxide lasers are rather large laser sources that can only be frequency tuned in a discrete manner, thus limiting the number and type of molecules that can be observed with a single instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Early LHRs used carbon dioxide gas lasers or lead salt lasers as the mid-infrared (mid-IR) local oscillators (LOs) and successfully targeted atmospheric ozone (O 3 ), nitrous oxide (N 2 O), and methane (CH 4 ) [4][5][6][7][8][9]. However, carbon dioxide lasers are rather large laser sources that can only be frequency tuned in a discrete manner, thus limiting the number and type of molecules that can be observed with a single instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Optical heterodyne spectroradiometry has successfully been used to measure stratospheric ozone from the ground using either a CO 2 laser or lead salt lasers as local oscillators [3][4][5][6]. As QCLs have become matured infrared sources, we developed a groundbased prototype LHR to evaluate the performance of QCL-based optical heterodyne radiometry for remote sensing, with the long term prospect of satellite deployment.…”
Section: Introductionmentioning
confidence: 99%
“…The number of the sounding altitude is equal to that of the sounding frequency, namely the i-th frequency vi is determined so that the weighting function W (z, v) has a maximum value at i-th altitude zi when v=vi, for i=1, 2,... , N. The Eq. (2) then can be written as, We solve these equations using the iterative inversion method first suggested by Chahine (1970) for remote sounding of atmospheric temperature by satellite observation, and later developed by Abbas et al (1978Abbas et al ( , 1979 for remote sounding of atmospheric minor constituents by high resolution spectroscopy. The algorithm has the following procedures.…”
Section: Inversion Methodsmentioning
confidence: 99%
“…Frerking and Muehlner (1977) first succeeded in measuring solar absorption spectra of atmospheric ozone in the wavenumber region around 1010 cm-1 with a tunable diode laser heterodyne spectrometer. Abbas et al (1978) showed a vertical profile of atmospheric ozone retrieved from a spectrum measured with a C02 laser heterodyne spectrome-ter. Further, Abbas et al (1979) developed an inversion method for high resolution atmospheric spectra, and applied it to the retrieval of an ozone profile from a spectrum observed with a tunable diode laser heterodyne spectrometer.…”
mentioning
confidence: 99%